Juvenile polyposis syndrome in a child with von Willebrand disease: a case report and literature review - Yang, Yang; Chen, Qiong (Frontiers in Pediatrics, 2025)
BackgroundJuvenile polyposis syndrome (JPS) is a rare autosomal dominant genetic disorder characterized by multiple gastrointestinal juvenile polyps. Endoscopic polypectomy is the primary therapeutic approach, minor post-polypectomy bleeding is the most common complication. We report an exceptional case of massive hemorrhage (approximately 400 ml) in a child with JPS.The cause of the post-polypectomy bleeding was relatively rare and was ultimately diagnosed as von Willebrand disease (VWD).Case presentationA six-year-old girl with JPS and no prior bleeding history underwent endoscopic polypectomy for 11 colorectal polyps.Laboratory tests showed normal platelet count, activated partial thromboplastin time (APTT), prothrombin time (PT), and plasma fibrinogen levels. However, approximately 70 hours after endoscopic polypectomy, she developed hematochezia with significant blood loss (approximately 400 ml). Emergent endoscopic findings did not support technical complications (e.g., clip dislodgement) as the primary etiology of the post-polypectomy hemorrhage.Genetic testing identified a mutation in the von Willebrand factor (VWF) gene [c.1707(exon14)delC, heterozygous], leading to a diagnosis of type 1 von Willebrand disease, which subsequently led to the unexpected post-polypectomy bleeding.ConclusionThe rare case of juvenile polyposis syndrome with von Willebrand disease in a child underscores the necessity of taking extrinsic gastrointestinal factors into account when delayed post-polypectomy bleeding arises following endoscopic polypectomy. Clinicians ought to be watchful for coagulation disorders, such as VWD, which might be manifested through atypical clinical symptoms. Timely identification of the cause of delayed post-polypectomy bleeding can improve prognosis.